The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1017/s1366728912000235
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic equivalence in the acquisition of /l/ by Spanish–English bilingual children

Abstract: Spanish [l] is characterized as clear, and is associated with a high second formant (F2) frequency and a large difference between F2 and the first formant (F1) frequencies. In contrast, English [l] is darker (with a lower F2 and a relatively smaller F2–F1 difference) and also exhibits contextual variation due to an allophonic velarization rule that further darkens [l] postvocalically. We aimed to determine if Spanish–English bilingual children evidence these differences productively, in a manner compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 105 publications
5
28
0
Order By: Relevance
“…Barlow et al . () found that the acoustic features of Spanish–English bilingual children's production of the phoneme /l/ in English differed from the features of /l/ production in English‐speaking monolingual children. Thus, our broad phonetic transcription may not have captured ways in which bilingual children's production of sounds is perceived to be in some way non‐native or ‘accented’ and thus difficult for adults to understand.…”
Section: Discussionmentioning
confidence: 96%
“…Barlow et al . () found that the acoustic features of Spanish–English bilingual children's production of the phoneme /l/ in English differed from the features of /l/ production in English‐speaking monolingual children. Thus, our broad phonetic transcription may not have captured ways in which bilingual children's production of sounds is perceived to be in some way non‐native or ‘accented’ and thus difficult for adults to understand.…”
Section: Discussionmentioning
confidence: 96%
“…F2-F1 values serve as an indicator of a vowel’s corresponding position in the oral cavity along the vertical and anterior-posterior dimensions [103–105]. Acoustic qualities of vowels are affected more by the gender of the speaker at the F0 level than at higher F1 and F2 formant bandwidths [105]. Moreover, vowel normalization procedures have been less effectively applied to multiple formant frequencies than to altering one single frequency (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely established that a bilingual’s two languages interact; this interaction happens during the acquisition process for both children and adults, and continues after the languages have been mastered with native-like competence (Paradis, 2001a, b; Cook, 2003; Flege et al, 2003; Fabiano and Goldstein, 2005; Flege, 2007; Barlow et al, 2013). Such interaction has been described at numerous levels of linguistic structure, from pragmatic to syntactic to lexical to phonological (e.g., Pavlenko and Jarvis, 2002; Cook, 2003; Dussias, 2003; Flege et al, 2003; Dussias and Sagarra, 2007; Flege, 2007; Amengual, 2012).…”
Section: Introductionmentioning
confidence: 99%